Perancangan Penyimpanan File Berbasis Cloud Di Kantor Desa Klambir Lima Kebun - Juliandri Juliandri; Barany Fachri; Hendry Hendry (Jurnal Media Infotama, 2022)
Data storage that is not centralized and less dynamic in being accessed by village officials, this is a problem when during the COVID-19 pandemic, work is done online. The research utilizes existing technologies such as the Cloud, so there is no need to provide a local server and access it using a public IP. The cloud used for storage will be installed with Linux Ubuntu 20 in it, then the OwnCloud feature will be configured in it, so that important files in the village office will be uploaded via the owncloud application which can be accessed by the public. The next stage is that each village apparatus will be given access rights according to the position in the village office. It is hoped that this research can support efforts to improve information technology in the village.